Analisis Proses Pembelajaran Matematika Berdasarkan Kurikulum 2013 pada Materi Pokok Peluang Kelas X SMA Negeri 1 Surakarta - Adi Wahyu Kuncara; Imam Sujadi; Riyadi Riyadi (Jurnal Pembelajaran Matematika, 2016)
Abstract: The aims of research was to describe the teacher understanding of 2013 curriculum-based learning process and assessment, learning process and assessment based on the 2013 curriculum in main subject of probability in classroom X SMA Negeri 1 Surakarta. This research used the qualitative method with the case study approach, by deeply studying the learning activities so as to describe the learning process taking place in the mathematics learning, especially the material of probability. The subject of research was mathematics teacher of the tenth grade of SMA Negeri 1 Surakarta with the criterion of having attended the training about 2013 curriculum. The data in this study were: (i) teacher’s understanding of the learning and assessment process based on 2013 curriculum (ii) mathematics learning process that imparting knowledge, attitudes, and skills with scientific approach (iii) the assessment process of knowledge, attitudes, and skills. Step analysis of the data in the study carried out in three stages, namely data reduction, data presentation, and withdrawal conclusion. The results of this study are as follows. (i) The learning process in curriculum 2013 was centered on the students, and the teacher merely functions as a facilitator. In addition, the learning process was not the only aspect of the knowledge imparted to students but the learning process in 2013 curriculum inculcate attitudes and skills aspects as well. According to teacher, assessment process using the aspects of knowledge, it can be a matter of testing and instrument description, aspects of attitude by observing and instrument in the form of sheets of observations, as well as aspects of skills with the practice tests or portfolios and instrument in the form of a rubric. (ii) Observed activities carried out by asking the students to listen to the explanation given by the teachers. The questioning activities carried out by asking questions to the students related to the material being studied. Information gathering activities that occur are students reading books and worksheets to answer the question or questions given by teacher. In this information gathering activities of teachers instill active attitude to the students. Inform process activities occur that students use information obtained from books and worksheets to answer the questions given by the teacher. On inform process activities, teachers inculcate cooperation and responsibility to the students. Communicated activities carried out by asking students to write the results of group discussions in class. (iii) Knowledge assessment process conducted by giving a quiz to the student at the end of learning and the instrument that is used in the form of a description. The attitude assessment process was carried out during the learning process. Teachers assess students attitudes to the observation technique. Skills assessment process were carried out during the learning process. Teachers assess students skills when communicating with the activities of the students and see the results of the discussion by looking at the results of the quiz given to students.Keywords : mathematics learning process, scientific approach, assessment process, curriculum 2013